Etude hydrobiologique du bassin de Marennes-Oléron : incidences sur la reproduction de Crassostrea gigas en 1977 - Berthome, Jean-paul; Razet, Daniel; Garnier, Jacqueline (ICES, 1978. Report of the Working Group, 1978)
The detection of larval oysters emissions and their evolution were studied in the Seudre river along with meteorological and bydrobiological datas. The earlier oyster emissions were found betveen july 4th and 8th and they developed into the fixation of the spat from july 14. The bydrobiological datas were correlated with one another as well as with the quantity of larval that was observed at each stage of their evolution. In the latter case, no significant correlation was established between the quantity of larval and the hydrobiologica.l datas, as those have undergone relatively few variations during time of the study. La détection des émissions larvaires et leur évolution ont été étudiées en Seudre en relation avec les paramètres météorologiques et hydrobiologiques. Les premières émissions de larves d'huîtres ont été détectées entre le 4 et le 8 juillet et ont conduit à des fixations de naissain à partir du 14 juillet Les données hydrobiologiques ont été correlées entre elles ainsi qu'avec les quantités de larves observées à chaque stade de leur évolution. Dans ce dernier cas, aucune corrélation significative n'est apparue entre le nombre de larves et les paramètres hydrobiologiques, ceux-ci ayant relativement peu varié an cours de la période étudiée.